Clinical outcomes of children with acute asthma and pneumonia in Mulago hospital, Uganda: a prospective study - Nantanda, Rebecca; Ostergaard, Marianne S; Ndeezi, Grace; Tumwine, James K (BMC Pediatrics, 2014)
Little attention has been paid to asthma in ‘under-fives’ in Sub-Saharan Africa. In ‘under-fives’, acute asthma and pneumonia have similar clinical presentation and most children with acute respiratory symptoms are diagnosed with pneumonia according to the WHO criteria. The mortality associated with acute respiratory diseases in Uganda is high but improving, dropping from 24% in 2004 to 11.9% in 2012. We describe the immediate clinical outcomes of children with acute asthma and pneumonia and document the factors associated with prolonged hospitalization and mortality. Methods: We enrolled 614 children aged 2 to 59 months with acute respiratory symptoms presenting at the emergency paediatric unit of Mulago hospital. Clinical histories, physical examination, blood and radiological tests were done. Children with asthma and bronchiolitis were collectively referred to as ‘Asthma syndrome’. Hospitalized children were monitored every 12 hours for a maximum of 7 days. Survival analysis was done to compare outcome of children with asthma and pneumonia. Cox regression analysis was done to determine factors associated with prolonged hospitalization and mortality.
Keywords: Asthma, Pneumonia, ‘Under-fives’, Duration of hospitalization, Mortality